Policy Implementation Selection of Prospective Government Employees with Employment Agreements (PPPK) in the Government Environment Central Sulawesi Province in 2023 - Gunawan, Rudy; Riadi, Slamet; Tawil, Muzakit (CV RIFAINSTITUT, 2025)
This study aims to analyze the implementation of the selection of candidates for Government Employees with Employment Agreements (PPPK) in the Central Sulawesi Provincial Government in 2023 and identify the factors that are obstacles in the selection process. The research method used is a qualitative approach with descriptive analysis, using the theoretical framework of van Meter and van Horn to examine the stages and factors of policy implementation. Data was collected through interviews, documentation, and direct observation on the implementation of PPPK selection. Data analysis is carried out by means of data collection, data reduction, data presentation, and interactive conclusions/verifications until data saturation is achieved. The results of the study show that the implementation of PPPK selection includes several stages ranging from planning to appointment, but there are obstacles such as differences in perception of the definition of the former THK-II, low graduation rate (40%), less effective communication, and lack of involvement of external supervisors. Data analysis revealed that inconsistent information and lack of socialization led to applicant unpreparedness, which resulted in a spike in registrations at the end of the time resulting in technical glitches on the server. In addition, economic, social, and political conditions are not paid much attention, especially in providing space for people's aspirations. All of these obstacles show the need to improve communication, supervision, and public participation so that the implementation of the PPPK selection policy can run more optimally